2015
DOI: 10.1063/1.4936385
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced quality factor of Fano resonance in optical metamaterials by manipulating configuration of unit cells

Abstract: By changing unit cell configurations, we demonstrated enhancement of quality factors (Q-factors) of Fano resonance in optical metamaterials composed of asymmetric double bars. The Q-factors of Fano resonance at wavelengths around 1500 nm were extracted from absorption spectra, and the dependence of the degree of asymmetry was studied. Observed enhancement is qualitatively interpreted by dipole-dipole interactions, and destructive interactions were essential for achieving high Q-factors. These results will be u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…An approach would be to manipulate the configuration of unit cells in the metamaterial array to mitigate radiative losses. It was reported that by alternating or inverting an asymmetric dipole bars (which constitute to one of the two sub‐unit cells) and placing it adjacent to neighboring asymmetric dipole bars, an enhancement in the Q ‐factor of Fano resonance is achieved. Based on the schematic of dipole–dipole interference, an enhancement in the Q ‐factor of Fano resonance in an alternating unit cell configuration was ascribed to destructive interference of dipole moments contributed by neighboring sub‐unit cells as illustrated in Figure c.…”
Section: Perspectives To Loss Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…An approach would be to manipulate the configuration of unit cells in the metamaterial array to mitigate radiative losses. It was reported that by alternating or inverting an asymmetric dipole bars (which constitute to one of the two sub‐unit cells) and placing it adjacent to neighboring asymmetric dipole bars, an enhancement in the Q ‐factor of Fano resonance is achieved. Based on the schematic of dipole–dipole interference, an enhancement in the Q ‐factor of Fano resonance in an alternating unit cell configuration was ascribed to destructive interference of dipole moments contributed by neighboring sub‐unit cells as illustrated in Figure c.…”
Section: Perspectives To Loss Engineeringmentioning
confidence: 99%
“…As a result, the net dipole moment of an alternating unit cell configuration is smaller than the nonalternating unit cell configuration. Therefore, the radiative loss in an alternating unit cell configuration is much lower, establishing a higher Q ‐factor . Quantitative analysis of complementary asymmetric double bars using multipole decomposition reveals that the linewidth narrowing of resonance in an inverted unit cell configuration is due to the competition between magnetic quadrupole and toroidal dipole.…”
Section: Perspectives To Loss Engineeringmentioning
confidence: 99%
“…The interactions among meta-atoms have great influence upon the Q-factor. Effects of different relative configurations of unit cells on the Q-factor of resonances have been studied in metallic metamaterials 15 , 21 23 , which have not been taken into account in all-dielectric metamaterials yet.…”
Section: Introductionmentioning
confidence: 99%
“…9 EIT is a quantum interference phenomenon that occurs in atoms interacting with electromagnetic fields, 10,11 and various types of metasurfaces and metamaterials that mimic EIT have been intensively studied. [12][13][14][15][16][17][18][19][20][21][22] An important feature of this EIT-like metasurface, which is composed of two types of radiatively a) Electronic mail: tamayama@vos.nagaokaut.ac.jp coupled cut-wire resonators, is the local electric field enhancement, which is stronger than that in a metasurface composed of only one type of cut-wire resonator (Lorentz-type metasurface) because of the compression of the electromagnetic energy density associated with the low-group-velocity propagation. This implies that studying EIT-like metasurfaces and metamaterials may lead to the development of a useful method for plasma generation.…”
Section: -8mentioning
confidence: 99%